2019
DOI: 10.1088/1755-1315/370/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and feeding habits of Euthynnus affinis, Auxis thazard, and Auxis rochei in South Coast of East Java waters

Abstract: Little tuna landed there are three types: Euthynnus affinis, Auxis thazard, Auxis rochei. The analysis shows the condition of the resource indicates the condition Over Exploited. Length and weight relationship tuna (Auxis thazard) total positive allometric Length of first caught fish (Lc) of 27.08 cm, The length at first maturity (Lm) 28.39 cm Lt = 35.40 {1 − e −0.58(t + 0.26)}, total mortality (Z) = 4.08 per year, Fishing mortality (F) = 2.91 per year, natural mortality (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…4). The lowest value (ɸ' = 4.8) was associated with the lower L ∞ (354 mm) estimated for the Indonesian population (Lelono and Bintoro, 2019).…”
Section: Age and Growth Parametersmentioning
confidence: 77%
See 3 more Smart Citations
“…4). The lowest value (ɸ' = 4.8) was associated with the lower L ∞ (354 mm) estimated for the Indonesian population (Lelono and Bintoro, 2019).…”
Section: Age and Growth Parametersmentioning
confidence: 77%
“…Growth rate was similar and particularly high for maximum age in the Indian Ocean, where data was estimated using length frequency analysis (Kasim, 2002;Abdussamad et al, 2005;Ghosh et al, 2010;Mudumala et al, 2018). The exception is the most recent report by Lelono and Bintoro (2019), where the growth rate was 0.58 year À1 for frigate tuna caught in two landing sites off the Indonesian coast. Taiwanese estimates were also lower (k = 0.50-0.52) and similar to one another, despite using length frequency analysis and vertebrae, respectively (Lu et al, 1991;Tao et al, 2012).…”
Section: Age and Growth Parametersmentioning
confidence: 97%
See 2 more Smart Citations
“…In Taiwan Strait, the dominant age of frigate tuna was two years (Tao et al, 2012). Numerous studies conducted in different parts of the world oceans revealed that this tuna species showed positive allometric growth (Ghosh et al, 2012;Tampubolon et al, 2016;Mariyasingarayan et al, 2018;Mudumala et al, 2018;Petukhova, 2019;Lelono & Bintoro, 2019;Herath et al, 2019).…”
Section: Introductionmentioning
confidence: 99%